The protective effect of common fig (Ficus carica L.) leaves extract on testes of white rats (Rattus norvegicus) against paracetamol (Acetaminophen) drug. - Noori Taha Alkhafaji; Waad Sabri Shaher (Tikrit Journal of Pure Science, 2020)
Aim :This study to investigate the protective effect of Ficus carica leaves extract against the effect of paracetamol. Material and methods:In the present study used (40) male rats (Rattus norvegicus) (2.5-3) months old, weighting (200-250)g were randomly divided into (4) groups of (10 rats/group). The first group (control group), the second group (paracetamol group), the third group (Fc leaves extract group), the fourth group (Fc leaves extract + paracetamol group) . the first group were given (0.5 ml) distilled water, the second group were given paracetamol with dosage (1000 mg/kg) , the third group were given alcoholic extract of F. carica leaves by dosage (250 mg /kg ), the fourth group were given paracetamol by dosage (1000 mg /kg) and after two hours given (250 mg /kg) alcoholic extract of F. carica leaves, all groups were treated with doses between day and another for six weeks. Results:The results of the present study showed a significant decrease (P<0.05) to the relative weight of the testicles , the head and tail of the epididymis, the seminal vesicles of male rats in the paracetamol group compared with the control group and Fc leaves extract group, while showed treated by alcoholic extract of F. carica leaves after paracetamol an improvement in the relative weight of the testicles , the head and tail of the epididymis , the seminal vesicles in Fc leaves extract group and Fc leaves extract + paracetamol compared with paracetmol and control group. For the histopathological study showed occurrence histopathological changes of paracetamol drug , represented as complete stop of spermatogenesis, atrophy and hypoplasia of leydig cells, congestion of blood vessels, pyknosis of nucleus of primary spermatogonia, hemorrhage between seminferous tubules, tunca albugenia and exfoliation of seminferous tubules as cellular debris. Conclusions: The paracetamol led to pathological changes in the tissues of male rat testes. It was represented by a complete cessation of spermatogenesis and a loss of the developmental stages of this process,while The alcoholic extract of F. carica leaves had protective effect against the influence of paracetamol.